(untitled) (قضايا سياسية, 2025)
The withdrawal of international coalition forces from Iraq entails significant political, economic, and security ramifications. Politically, the withdrawal may lead to a deterioration of stability within the country, as internal conflicts and tensions among various factions escalate. This deterioration could impact the Iraqi government's ability to make effective decisions and achieve national consensus. Economically, Iraq may experience negative effects, including a decline in foreign investments and decreased oil revenues, further exacerbating financial challenges faced by the government and undermining reconstruction and development efforts. From a security standpoint, the withdrawal of the international coalition may result in an escalation of security threats, as armed groups seize the opportunity to increase their activities and escalate attacks, posing a threat to the daily lives of civilians and hindering reconstruction and development efforts. Therefore, the withdrawal of international coalition forces represents a significant challenge to the political, economic, and security processes in Iraq, necessitating effective strategies to address the challenges arising from this withdrawal.